Subsídios para o manejo da atividade de escalada no Parque Nacional dos Campos Gerais (PR) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
The practice of climbing is highlighted in the area comprising the Campos Gerais National Park (CGNP). The fact is justified by the variety of rocky outcrops present in the region. Because it is a Conservation Unit of integral protection, the practice of this activity must be planned and regularized to reconcile the preservation of nature with the visitation. Based on this, the present research has as general objective to suggest rules of public use necessary for the accomplishment of the escalation in CGNP. For this, bibliographical research and in loco researches (interviews and field trips) were carried out, which determined the spatial cut of the research. The Chico Mendes Institute for Biodiversity Conservation points to seven consolidated areas with public use, a practice that was already in place long before the National Park was created in 2006. Of these areas, five were identified with climbing: Cachoeira do Rio São Jorge , Boulder Serrinha, Padre's Hole, Pasta Sector and Dolina Grande. The diagnosis of the areas with the climbing activity was carried out according to the Methodological Roadmap for the Management of Visitation Impacts (ICMBIO, 2011). To complement the main objective, the structured questionnaire was carried out with questions pertinent to the profile of the climbing practitioner, also questions related to the behavior of the climbers. The questionnaire was based on a survey of climbers in the New River Gorge region of the United States (MCKENNEY, 2013). The questionnaire was applied to thirty climbers, and identified the demographic profile and low impact behavior of the practitioners. It was found that 95.8% of the interviewees felt it was their responsibility to share responsibility for the maintenance of climbing areas, demonstrating the high degree of identity with the PNCG. And, finally, based on the national parks that already have the climbing activity properly instituted, management recommendations were elaborated.
Keywords: Unidades de Conservação; Parque Nacional; Uso público; Manejo de áreas protegidas; Conservation Units; National Park; Public Use; Management of Protected Areas; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA